SISTEM PENGELOLAAN KEARSIPAN DEBITUR DI UNIT ADC PT. BANK NEGARA INDONESIA (Persero) Tbk. KANTOR CABANG MARGONDA - Tatyana Tatyana (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2020)
In managing records at the ADC Unit of PT. Bank Negara Indonesia (Persero) Tbk. The Margonda Branch Office itself already has a special storage room for debtor archives, but the filing of the shelf is not neatly arranged in alphabetical order so it is messy and less well organized. It also makes it difficult to find files that you want to reuse. In its implementation, there is no archivist who handles archives, thus hindering the management of archives and ADC Unit employees who also manage debtor archives. That is what makes debtor archives management less well because of the large amount of work done by the ADC Unit, it must also manage archives so that the management of the archives is less attention. PT. Bank Negara Indonesia (Persero) Tbk. (hereinafter referred to as 'BNI' or 'Bank') was originally established in Indonesia as a central bank under the name "Bank Negara Indonesia" based on Government Regulation in Lieu of Law No. 2 of 1946 dated 5 July 1946. Furthermore, based on Law no. 17 of 1968. BNI was designated "Bank Negara Indonesia 1946" and the status was a State-Owned Commercial Bank. The ADC unit has an archive storage room located in a special room in accordance with standardization, the principle of archive management used is decentralization, the types of documents that are managed in the archive storage room are the debtor's work files and the debtor's original files.